Exploring graduate student roles and responsibilities in enhancing sense of belonging in residence life during COVID‐19. Issue 176 (28th February 2022) - Hernández, Erin; Kalstrom, Benjamin; Murray, Abigail; Nelson, Zoe; Squire, Dian
Abstract: Based on an autoethnographic study, this article aims to better understand how graduate student residence life staff made sense of their responsibilities and roles in enhancing student belonging within residence halls. The article also explores how the graduate students' own sense of belonging was impacted as a result of COVID‐19 policy.